2006
DOI: 10.1016/s0828-282x(06)70265-3
|View full text |Cite
|
Sign up to set email alerts
|

Stroke prevention in patients with atrial fibrillation: The diagnosis and management of hypertension by specialists

Abstract: BACKGROUND: Hypertension is common in patients with atrial fibrillation (AF) and is an important cause of stroke. OBJECTIVES: To determine how effectively hypertension is managed among specialist-treated outpatients with AF. METHODS: Investigators reviewed the charts of patients with a diagnosis of AF cared for by medical specialists to determine the change in blood pressure, patterns of antihypertensive drug use and the role of the specialist in the management of hypertension. RESULTS: Of 209 patients with AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Randomized clinical trials have previously demonstrated improved outcomes in diabetic patients with a better blood pressure (BP) control, especially at systolic BP treatment goal of 130 to 135 mm Hg [35,36]. However; in RE-LY, 1014 (24%) and 1918 (45%) patients with DM had a systolic blood pressure of more than 140 mm Hg and 130 mm Hg, respectively suggesting that improved diagnosis and management of hypertension could be an important, additional means of stroke prevention among patients with AF and DM [37].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials have previously demonstrated improved outcomes in diabetic patients with a better blood pressure (BP) control, especially at systolic BP treatment goal of 130 to 135 mm Hg [35,36]. However; in RE-LY, 1014 (24%) and 1918 (45%) patients with DM had a systolic blood pressure of more than 140 mm Hg and 130 mm Hg, respectively suggesting that improved diagnosis and management of hypertension could be an important, additional means of stroke prevention among patients with AF and DM [37].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 22 23 ] The characteristics of patients as reported in these studies are summarized in Table 4 . [ 20 21 24 25 26 27 28 29 30 31 ] The mean age of patients with AF in studies conducted in different regions have ranged from 64 years to 82 years,[ 20 21 22 23 24 25 26 27 28 29 30 31 32 ] whereas the patients in both groups of this study were younger, i.e., 52 and 63 years old, with comparable mean BMI (29 and 32 kg/m 2 ) to that reported in the published data (range of 25-32 kg/m 2 ) as shown in Table 4 . Smoking among patients with AF ranged from 5.5% in European subjects[ 20 ] to 16% in the Japanese counterparts,[ 26 ] while the percentages in the present study varied between the two groups, i.e., 8% and 15.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian study, the authors reviewed the patient charts of four electrophysiologists, three cardiologists, and six internists, working in the same University hospital [65]. Although important for the proper conduction of these trials, this may result in suboptimal attention to common conditions like hypertension.…”
Section: The Role Of Physician Hyperspecializationmentioning
confidence: 99%